2007
DOI: 10.1111/j.1532-5415.2007.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vision to Prevent Falls in Frail Older People: A Randomized Trial

Abstract: In frail older people, comprehensive vision and eye assessment, with appropriate treatment, does not reduce, and may even increase, the risk of falls and fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 22 publications
0
108
0
4
Order By: Relevance
“…The measures of vision add information on sensory function to these measures of motor function and vitality, thus complementing each other and adding sensitivity to the combined biomarker of aging (frailty) index. Province et al (1995), Gillespie et al (2001), Li et al (2005), Faber et al (2006) suggested that significant improvements in risk of falls can be achieved through exercise programs, although this finding is not universal (Cumming et al, 2007). However, there have been few studies aimed at decreasing the risk of falls by improving visual function (Day et al, 2002;Harwood et al, 2005;Foss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measures of vision add information on sensory function to these measures of motor function and vitality, thus complementing each other and adding sensitivity to the combined biomarker of aging (frailty) index. Province et al (1995), Gillespie et al (2001), Li et al (2005), Faber et al (2006) suggested that significant improvements in risk of falls can be achieved through exercise programs, although this finding is not universal (Cumming et al, 2007). However, there have been few studies aimed at decreasing the risk of falls by improving visual function (Day et al, 2002;Harwood et al, 2005;Foss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these have been limited by the poor followup for treatment (Day et al, 2002) or dealt only with cataract surgery (Harwood et al, 2005;Foss et al, 2006). The randomized controlled trial by Cumming et al (2007) took a more comprehensive approach to diagnosing and intervening upon vision abnormalities for the prevention of falls in older adults. The findings from that study were disappointing in that the intervention group fared no better than the control with respect to falls in the following year.…”
Section: Discussionmentioning
confidence: 99%
“…Even an intervention that is in widespread use, such as multi-disciplinary team assessment has been shown to be effective in some studies, 66 but not in others. 65,67 As discussed earlier, interventions may affect subsequent behaviour or activity level in an individual, possibly confounding the results, and ideally this needs to be controlled for.…”
Section: Cummings 67mentioning
confidence: 99%
“…The simplest method with impaired vision becomes choosing the right quality and parameters of lenses for glasses, giving a guarantee of better visibility and confidence in movement. Correctly matched glasses reduce the number of falls (Cumming et al 2007). Treatment of eye diseases is indispensability, immediately performing the necessary surgery for example cataracts increases the field of view, the quality of functioning and thus reduces the risk of falls, compared to people waiting a long time for the procedure in which more often injury occur (Harwood et al 2005 ;Foss et al 2006).…”
Section: Impaired Visionmentioning
confidence: 99%